A public health approach to gun violence: evaluating strategies to improve intervention and public awareness - Spinrad, Michael (2017)
The United States is experiencing a significant public health problem in the form of gun violence. Despite being one of the wealthiest countries in the world, the US exhibits significantly higher rates of fatal and non-fatal firearm injuries than other wealthy, industrialized nations. Despite this issue, the debate on gun control is one of the most heated topics discussed across the political spectrum. The constitutional right to own and possess a firearm is defended fiercely by gun advocates that desire fewer restrictions. The content of this thesis provides a detailed overview on the history of gun control through the 20th and 21st century. Current evidence on four major classifications of gun violence: homicide, suicide, non-fatal firearm injuries, and mass shootings are then presented, followed by a brief of discussion of commonly perceived risk factors for gun violence. After the context of gun violence has been defined, the thesis explores several strategies and preventative measures found within the literature. The available data is limited by a lack of research on gun violence. Although inferring true efficacy was limited, based on the established knowledge of prevalence and risk factors for gun violence some conclusions could be made. The expansion of the national background check, along with updated definitions for exclusion criteria could provide the most immediate and far reaching reduction in gun violence. While it was difficult to prove other solutions as effective, good communication and raising awareness could increase implementations of strategies designed to limit gun violence. Well-constructed media campaigns and messages are proposed for raising awareness of the risk factors for gun violence and to promote the public’s interest in research and prevention